Sustainable local development in the "E" syllabus diagnostic conception - Vilma María Pérez Viñas; Benito Bravo Echevarría; Arturo Pulido Díaz; Taymí Breijo Worosz (Cooperativismo y Desarrollo, 2020)
The continuous improvement of the quality of professional training, aimed at sustainable local development, is one of the social tasks of the contemporary university. Consequently, Higher Education institutions need to diagnose the management of the training processes they develop. This article intends to offer a conception for the diagnosis of the management of the implementation of the "E" syllabuses, in the University of Pinar del Río "Hermanos Saíz Montes de Oca", that reassesses the sustainable local development in the initial professional formation and guarantees the real knowledge about this process with truthful and sufficient information, that allows redirecting it according to the fulfillment of the established purposes. The methods used were the documentary analysis and the Vigotskian methodology of the complex units of analysis that allowed to establish the main relations and components of this process. As a result, the study variable was defined and five dimensions were identified: institutional, administrative, pedagogical, community and methodological, with the corresponding indicators. The methods proposed for carrying out the diagnosis were documentary analysis, observation, survey, interview and pedagogical test to be measured with a two-level scale: satisfactory and unsatisfactory. This conception of the diagnosis of the management of the "E" syllabus is an effective tool to improve the quality of university professional formation in Cuba, which is particularly relevant in times when they demand curricular flexibility, essentiality of contents, self-learning and impact on local development with sustainability criteria.